The role of information asymmetry in the choice of entrepreneurial exit routes - Dehlen, Tobias; Zellweger, Thomas; Kammerlander, Nadine; Halter, Frank (Journal of Business Venturing, 2014)
Our quantitative study investigates the determinants of internal versus external exit routes in family firms. Building on information asymmetry theory, we examine how an owner's inferior knowledge about the abilities of potential external entrants (in contrast to family internal successors) renders a family internal transfer more likely. This information asymmetry, however, can be mitigated by activities such as owners' screening and transfer candidates' signaling efforts to reveal the candidates' abilities. Our data exhibits a positive effect of signaling and an inverted U-shaped effect of screening on the probability of external exit routes. Firm age, as a driver of emotional attachment, weakens these effects.